A Mixed-Methods Inquiry into Faculty Commitment: Exploring Institutional and Organizational Predictors for Evidence-Based Policy Reforms - Trinidad, Amelie E. (International Journal of Learning, Teaching and Educational Research, 2025)
Faculty commitment is essential to institutional effectiveness, teaching quality, and long-term academic workforce engagement. In the Philippine context, limited research has examined how institutional and organizational factors interact to influence faculty commitment. This study addresses that gap by investigating how autonomy and decentralization (institutional characteristics) and perceived organizational support and fairness (organizational experiences), shape affective, continuance, and normative commitment among college faculty. Guided by Meyer and Allen’s Three-Component Model and the Job Demands–Resources (JD-R) framework, the study employed a convergent parallel mixed-methods design. Quantitative data were collected through validated surveys from 154 faculty members, while qualitative data were gathered via semi-structured interviews with ten purposively selected participants. Results revealed that organizational experiences, especially perceived support and fairness, were the strongest predictors of commitment. Institutional characteristics also had significant effects, particularly on affective and normative dimensions. Affective commitment emerged as the most dominant across both data strands. The convergence of results confirmed that emotional attachment is most influenced by trust, recognition, and participative governance. Quantitative findings were reinforced by faculty narratives describing institutional respect and inclusive environments as drivers of loyalty and motivation. These findings support evidence-based policy reforms that emphasize shared governance, academic autonomy, and equitable treatment to enhance faculty commitment and institutional performance. https://doi.org/10.26803/ijlter.24.8.30